Transesophageal echocardiography in the emergency department: A comprehensive guide for acquisition, implementation, and quality assurance - Duncan McGuire; Steven Johnson; Nicholas Mielke; Amit Bahl (Journal of the American College of Emergency Physicians Open, 2022)
Abstract Echocardiography is an essential tool in emergency medicine, yielding valuable information for physicians that directly affects diagnostic and management strategies. Emergency department (ED) transesophageal echocardiography (TEE) is an increasingly common procedure performed in a variety of institutions, allowing for ongoing cardiac imaging during cardiopulmonary resuscitation as well as providing high‐resolution assessment of both cardiac and aortic anatomy. However, despite the numerous benefits of ED TEE, the process of implementing this modality within a department is difficult because of unique process and cost considerations. This paper serves to provide an updated and in‐depth description of these processes to assist with the initiation of such a program, including a detailed discussion of budgetary considerations, physician credentialing, and device use and maintenance protocols.